Bioactivities of Calocybe indica Protein combined with Cell-Free Supernatant of Lactobacilli from a Fermented Cereal against Free Radicals and Microorganisms - Taiwo Scholes Adewole; Clement Olusola Ogidi; Adenike Kuku (Journal of Food Bioactives, 2022)
Edible fungi and lactic acid bacteria (LAB) are emerging as reservoirs of diverse bio-functional products. This study investigated antioxidant and antimicrobial activities of a mushroom; Calocybe indica protein (CIP) and cell-free supernatant (CFS) of Lactococcus lactis, Lactobacillus fermentum, and Lactobacillus brevis isolated from a fermented cereal food-Kati against free radicals and microorganisms associated with fruits spoilage. Protein extract from C. indica was subjected to ammonium sulfate precipitation (55% saturation). Synergistic radical scavenging activities of CIP and CFSs of LAB against 2,2’-azinobis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS˙+), 1,1-diphenyl-2-picrylhydrazyl (DPPH˙), hydroxyl radicals (OH˙) and their Fe2+ ion chelation activity were within 70.39-84.77%, 62.51-87.63%, 70.58-88.56%%,  and 62.83-78.76%, respectively. Combinatory effects of CIP and CFSs showed pronounced zones of inhibition of 6.5 mm to 12.1 mm against tested microorganisms. The study established that, bioactivities of C. indica and Lactobacilli can be attributed to their inherent bioactive proteins, suggesting their potential exploitation as natural bio-preservatives.